Modeling Conic Section Using Hawgent Dynamic Mathematics Software - Ning Yiting; Jianlan Tang; Rafiantika M. Prihandini; Usman Aripin (Institut Agama Islam Negeri Curup, 2022)
Teachers should pay attention to the deep integration of information technology and mathematics courses, so as to achieve the effect that traditional teaching methods are difficult to achieve. Conic section in high school is an important carrier for cultivating students' mathematical literacy, but it is highly abstract and comprehensive, making it a